Improving Waffle Quality through Substitution of Dragon Fruit Peel Flour - Anita Wulandari; Amelia Nirmalawaty (Postgraduate, University of Mataram, 2025)
Since 2019, the price of dragon fruit has often plummeted during peak harvest periods, causing farmers to delay harvesting or even discard the fruit into rivers. Various studies have been conducted to optimize the utilization of its bioactive compounds, such as proteins, fats, organic acids, and minerals, to address this issue. One such approach is utilizing dragon fruit peel as flour. This study aims to determine the optimal substitution percentage of dragon fruit peel flour (TKBN) in waffles to improve their quality through De Garmo's effectiveness test. Four levels of wheat flour substitution with dragon fruit peel flour were applied: 0% (P0), 3% (P1), 6% (P2), and 9% (P3), each replicated four times. The results showed that increasing the substitution of dragon fruit peel flour decreased the moisture and fat content in waffles, while protein, fiber, ash, and carbohydrate content increased. All organoleptic variables declined as the substitution level increased. It was concluded that a 6% substitution of dragon fruit peel flour significantly increased fiber, protein, carbohydrate, and ash content while reducing fat content, although the fat reduction was not statistically significant.